Islamic Banking and Loyalty: Service Quality, Intimacy or Religious Driven? - Yusfiarto Rizaldi; Nugraha Septy Setia; Pambudi Dwi Santosa; Pambekti Galuh Tri (Studies in Business and Economics, 2022)
Islamic banking is an essential element in the development and establishment of Indonesia’s economy, for that it is crucial for management to have a good marketing strategy to be sustainable. Thus, this research aims to explore the route of consumer loyalty by emphasizing religiosity, intimacy, and service quality as the factors of consumer satisfaction of Indonesian Islamic banking. This study applies a structural equation model (SEM) to analyze data collected from 308 Islamic bank consumers in Indonesian Islamic communities and Islamic institutions. The empirical results show that the service quality dimensions (PAKSERV scale); tangibility, reliability, assurance, sincerity, personalization, and formality play an essential role in increasing consumer satisfaction and consumer loyalty. There is no direct relationship between consumer religiosity and consumer loyalty, whereas consumer intimacy and service quality have a direct positive impact on consumer satisfaction and consumer loyalty. Furthermore, consumer satisfaction act as fully mediating role between service quality and consumer loyalty. Practically, the findings of this study can be used by Islamic banking management to focus on modifying service quality by emphasizing the dimensions of sincerity, personalization, and formality. And stay focused on the customer relationship with the company